针刺结合拔罐治疗哮喘50例 - 赵培君 赵志鹏 (世界针灸杂志：英文版, 2012)
Asthma is a common and multiple allergic lung disease. It usually occurs in autumn and winter, manifests as sudden distention and fullness of chest, and difficulty in breath. The authors have treated 50 cases of asthma with combined therapy of acupuncture and cupping from April 2002 to April 2011. It is summarized as follows.CLINICAL DATA General data All of the 50 cases were from outpatients of our hospital, of which, 29 cases were male and 21 cases were female;